Refining the genomic profiles of North African sheep breeds through meta-analysis of worldwide genomic SNP data - Baazaoui, Imen; Bedhiaf-Romdhani, Sonia; Mastrangelo, Salvatore; Lenstra, Johannes A; Da Silva, Anne; Benjelloun, Badr; Ciani, Elena (Frontiers in Veterinary Science, 2024)
The development of reproducible tools for rapid genotyping of thousands of genetic markers (SNPs) has promoted cross-border collaboration in the study of sheep genetic diversity in a global scale. In this study, we collected a comprehensive dataset of 239 African and Eurasian sheep breeds genotyped at 37,638 filtered SNP markers, with the aim of understanding the genetic structure of 22 Northern African (NA) sheep breeds within a global context. We revealed a substantial enrichment of gene pool between north and south shores of the Mediterranean Sea, which corroborate the importance of the maritime route in the history of livestock. The genetic structure of northern African breeds mirrors the differential composition of genetic backgrounds following the breed history. Indeed, Maghrebin sheep stocks constitute a geographically and historically coherent unit with any breed-level genetic distinctness among them due to considerable gene flow. We detected a broad east-west pattern describing the most important trend in NA fat-tailed populations, exhibited by genetic closeness of Egyptian and Libyan fat-tailed sheep to Middle Eastern breeds rather than Maghrebin ones. A Bayesian FST scan analysis revealed a set of genes with potentially key adaptive roles in lipid metabolism (BMP2, PDGFD VEGFA, TBX15 and WARS2), coat pigmentation (SOX10, PICK1, PDGFRA, MC1R and MTIF) and horn morphology (RXFP2) in Tunisian sheep. Local ancestry method detected a Merino signature in Tunisian Noire de Thibar sheep near SULF1gene introgressed by Merino's European breeds. This study will contribute to the general picture of worldwide sheep genetic diversity.